Effectiveness of the introduction of Proprioceptive Training in the exercise programs for Knee Osteoarthritis - Carrasqueira, A. R. (2018)
Trabalho apresentado em EULAR Annual European Congress of Rheumatology, 11-14 de junho 2014, Paris, França